Analisis Desk Research Startup : Perkembangan Dan Dukungan Program Pendanaan Di Indonesia - Diki Nanang Surahman (Brida Provinsi Jambi, 2025)
Indonesia is one of the most dynamic growth centers for the startup ecosystem in Southeast Asia. Limited access to financing often hampers startup growth and sustainability potential in Indonesia. Therefore, innovation strategies in financing or funding programs are key in overcoming these obstacles and paving the way for more significant developments. The approach taken in this research is qualitative, using desk research analysis by exploring data from various sources as secondary data. The results of the analysis show that funding has a positive and significant impact on startup business actors' growth development and sustainability. One of the funding sources is from the National Research and Innovation Agency through the Advanced Indonesian Innovation Research (RIIM) Startup funding scheme, which has funded 74 startups with a total funding of IDR 24 billion (2022 - 2024). Funding comes from BRIN and universities, ministries/institutions, and other research and development institutions. With strong support from various parties and Indonesia's increasingly mature startup ecosystem, the future and development of startup businesses in this country look increasingly bright. With innovation, creativity, and a strong entrepreneurial spirit, startup entrepreneurs in Indonesia are ready to conquer challenges and achieve success in the global business world. Keywords: desk research; funding; innovation; program; startup